Binding of lead to collagen type I and V and alpha2(I) CNBr (3,5) fragment by a modified Hummel-Dreyer method - Mikšík, Ivan; Deyl, Zdeněk; Herget, Jan; Novotná, Jana; Mestek, Oto (Journal of chromatography. A, Including electrophoresis and other separation methods, 1999)
Binding of lead (as lead acetate) to collagen type I alpha, and alpha2 chains, collagen type V and a large cyanogen bromide fragment of type I collagen [alpha2(I)CB(3,5)] was investigated by the large-zone Hummel-Dreyer method. It was demonstrated that two categories of binding sites exist in the collagen molecule, the number of which correlates rather well with the available aspartic and glutamic acid residues. Similar results were obtained for all collagen chains (fragments) used. The number of sites thus obtained was compared with the cross-striation pattern (reflecting areas where lead is bound) of the SLS form of collagen type I (alpha1 chain); it is suggested that the number of bands seen in the SLS form reflects primarily the number of available aspartic acid residues in the molecule. The association constants obtained are comparable with the low affinity interactions seen e.g., between Cu and bovine serum albumin.
Keywords: Cyanogen Bromide; kolagen; elektronová mikroskopie; bromkyan; Microscopy, Electron; Peptide Fragments; peptidové fragmenty; Collagen; olovo; Lead